1995
DOI: 10.1159/000179078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Administration of Purified Micronized Flavonoid Fraction on Increased Microvascular Permeability Induced by Various Agents and on Ischemia/Reperfusion in Diabetic Hamsters

Abstract: The effects of a clinically used purified micronized flavonoid fraction (S5682) containing 90% diosmin and 10% hesperidin on increased microvascular permeability induced by histamine, bradykinin and leukotriene B4 (LTB4) were investigated by intravital microscopy in the cheek pouch preparation of diabetic hamsters. We also investigated the effects of S 5682 on macromolecular permeability increase and leukocyte adhesion during ischemia-reperfusion using the same preparation. Diabetes was induced by an intraperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Hesperidin and diosmin, in combination, were found to decrease leukocyte adhesion to the endothelium in post capillary venules, after ischaemia/reperfusion, as assayed through skin fold window chamber in guinea-pigs following intragastric administration of the compounds (Friesenecker et al, 1994). This antiischaemic effect of hesperidin was again reported in the hamster, at a dose of 20 mg/kg body weight after intragastric administration (Bouskela and Donyo, 1995). In addition a micronized purified flavonoid fraction containing hesperidin and diosmin was found to significantly decrease ADPinduced platelet aggregation and increase platelet disaggregation, in rats.…”
Section: Platelet and Cell Aggregation Inhibitionmentioning
confidence: 67%
“…Hesperidin and diosmin, in combination, were found to decrease leukocyte adhesion to the endothelium in post capillary venules, after ischaemia/reperfusion, as assayed through skin fold window chamber in guinea-pigs following intragastric administration of the compounds (Friesenecker et al, 1994). This antiischaemic effect of hesperidin was again reported in the hamster, at a dose of 20 mg/kg body weight after intragastric administration (Bouskela and Donyo, 1995). In addition a micronized purified flavonoid fraction containing hesperidin and diosmin was found to significantly decrease ADPinduced platelet aggregation and increase platelet disaggregation, in rats.…”
Section: Platelet and Cell Aggregation Inhibitionmentioning
confidence: 67%
“…Studies in experimental animals have demonstrated that the histamine, bradykinin, leukotrienc B4 [3] and ischemia/reperfusion (I/R) [4]-induced increase in vascular permeability was inhibited by S-5682 given orally to hamsters for 10 days. When similar studies were performed in diabetic hamsters the inhibitory effect of S-5682 was even more pronounced [5], The anti inflammatory action of flavonoids is well known [6], In vitro studies on human neutrophils have shown that micronized diosmin may counteract phorbolester-induced chemiluminescence, a phenomenon inhibited by superoxide dismutase (SOD), thus suggesting that mi cronized diosmin has antioxidative properties by reacting with the superoxide anion [7], Various flavonoids were found to reduce the superoxide anion in vitro and it was suggested that the reactions between flavonoids and su peroxide anion constitute an efficient inactivation of the superoxide radical to produce hydrogen peroxide and flavonoid radicals [8]. The I/R-induced vascular permeabili ty increase in the hamster was effectively counteracted by EC-SOD and Cu.Zn-SOD [9] and by the nitric oxide (NO) synthase inhibitor.…”
Section: Introductionmentioning
confidence: 76%
“…In vitro studies of human cultured endothelial cells demonstrated the formation of ONOO~ peroxynitrite by topical stimula tion of human cultured endothelial cells with bradykinin [16]. Peroxynitrite may be formed by the reaction be tween the superoxide anion and NO [ 17], The bradykinininduced permeability increase was clearly inhibited by L-NA [18] and S-5682 [3][4][5], However, it remains to be shown whether one of these three oxygen species could be the target for the flavonoid antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…66 Diabetic animals exposed to I/R exhibit an exaggerated vascular permeability response that is accompanied by accelerated ROS production and more adherent leucocytes in post-capillary venules. 67,68 Whereas leucocytes have been implicated as a source of ROS in the post-ischaemic microvasculature of diabetic animals, 69 hyperglycaemia-induced overproduction of ROS by mitochondrial electron transport chain may also contribute to the exaggerated permeability response to I/R. 70 PAF and LTB4 have been implicated in the exaggerated leucocyte recruitment, 67,71 which involves CD11/CD18-ICAM-1 adhesive interactions (firm adhesion) and P-selectin (rolling).…”
Section: Diabetesmentioning
confidence: 99%